2022
DOI: 10.1186/s40164-022-00310-0
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omic profiling of the leukemic microenvironment shows bone marrow interstitial fluid is distinct from peripheral blood plasma

Abstract: Background The bone marrow is the place of hematopoiesis with a microenvironment that supports lifelong maintenance of stem cells and high proliferation. It is not surprising that this environment is also favourable for malignant cells emerging in the bone marrow or metastasizing to it. While the cellular composition of the bone marrow microenvironment has been extensively studied, the extracellular matrix and interstitial fluid components have received little attention. Since the sinusoids connec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Using data resampling, we also investigated the impact of sample size in a metabolomics study and found that having 5 samples in a metabolomics study is enough to purify half of the MS/MS spectra and effectively improve spectra quality (Text S7). , It should also be noted that the prediction performance of the trained XGBoost model might be reduced for metabolomics data generated in different LC/MS instruments. In particular, the intensity ratio RSDs used for prediction is instrument-dependent.…”
Section: Resultsmentioning
confidence: 99%
“…Using data resampling, we also investigated the impact of sample size in a metabolomics study and found that having 5 samples in a metabolomics study is enough to purify half of the MS/MS spectra and effectively improve spectra quality (Text S7). , It should also be noted that the prediction performance of the trained XGBoost model might be reduced for metabolomics data generated in different LC/MS instruments. In particular, the intensity ratio RSDs used for prediction is instrument-dependent.…”
Section: Resultsmentioning
confidence: 99%
“…In order to mitigate the presence of batch effects across distinct GEO datasets, we conducted batch correction on the amalgamated gene expression matrix. Subsequently, the efficacy of this correction was assessed through Principal component analysis (PCA) [ 17 ]. PCA is a method of statistics that employs orthogonal transformation to change possibly correlated variables sets into a linearly independent variables sets.…”
Section: Methodsmentioning
confidence: 99%